Circular migration or permanent return: What determines different forms of migration? - Florin P. Vadean; Matloob Piracha (University of Kent, Department of Economics, 2009)
This paper addresses the following questions: To what extent do the socio-economic characteristics of circular/repeat migrants differ from migrants who return permanently to the home country after their first trip (i.e. return migrants) and what determines each of these distinctive temporary migration forms? Using Albanian household survey data we find that education, gender, age, geographical location and the return reasons from the first migration trip significantly affect the choice of migration form. Compared to return migrants, circular migrants are more likely to be male, have primary education and originate from rural, less developed areas. Moreover, return migration seems to be determined by family reasons, a failed migration attempt but also the fulfilment of a savings target.
Keywords: C35; F22; J61; 330; return migration; circular migration; sample selection; Internationale Wanderung; Rückwanderung; Bildungsabschluss; Geschlecht; Albanien